Pelanggaran Maksim Kualitas Pada Program Acara Pesbukers Di Antv Edisi Desember 2014 Sebuah Kajian Pragmatik - Issyahra, Nindha; , Prof, Dr, Markamah M.Hum (2016)
This study aims to (1) describe a violation of the maxim of quality programs in antv Pesbukers December 2014 edition a pragmatic study, (2) describe implicatures for violations maxim of quality programs in the quiz show Pesbukers ecember 2014 issue a study of pragmatics. Data collection method used is the method agih. Data analysis techniques used in this study is the technique BUL (For Elements Lingual). The results of this study are as follows. First, the study found four forms of violations maxim of quality that is the violation maxim of quality in the form of taunting, violation maxim of quality in the form of blame, offense maxim of quality in the form of accused without strong evidence, breach maxim of quality in the form memelestkan. Secondly, it was found 17 types of mplicatures for violations maxim of quality is implicature affirm and mock, mock and ask the audience silent, mocking and inforce, mocking and justify, ridicule and preach, preach and affirm, mock and affirm, mocking and inform, ridicule and preach, and defending mock, taunt and change the subject, pleading and vilify, insult and show emotion, surprise and showed drowsiness, providing advice and mock, asking for help to show concern.